Increasing The Strength of Cellular Lightweight Concrete Bricks with The Addition of Bamboo Fiber - Magnolia, An-Nisa; Akmal, Jamiatul; Martinus, Martinus; Savetlana, Shirley; Helmi, Masdar (Jurnal Rekayasa Proses, 2024)
This research aims to obtain technology for improving the quality of CLC (Celullar Lightweight Concrete) bricks to be equivalent to AAC (Autoclaved Aerated Concrete). This is a response to the rapid development, especially in the property sector, which is followed by the increasing need for bricks as the main material for building walls. CLC bricks are an alternative product other than red bricks that have the potential to pollute the environment because in the production process there is burning. The problem is that the quality of CLC bricks is relatively lower compared to AAC bricks. The method is to add bamboo fiber as a reinforcement and optimize the elements. The design of the experiment was made using the Taguchi Method, but preliminary experiments had previously been carried out to predict the percentage of elements. The research includes manufacturing process technology and quality testing on samples. Bamboo fiber-reinforced CLC bricks are obtained with an optimal composition of 0.5% fiber and a ratio of cement mass to sand mass of 1:1.6. This sample has a compressive strength of 1.1235 MPa and a bending strength of 1.1723 MPa. From this composition, samples were obtained with an average compressive strength of 1.1285 MPa and an average bending strength of 1.3551 MPa. Thus, it can be concluded that the addition of fiber can increase the strength of CLC bricks to be equal to or stronger than AAC bricks on the market.